Proceedings of the International Workshop 'From Global Burden of Disease Studies to National Burden of Disease Surveillance'. Issue 5 (July 2016) - Scheidt-Nave, Christa; Ziese, Thomas; Fuchs, Judith; Plass, Dietrich; Achoki, Tom; Leach-Kemon, Katherine; Speyer, Peter; Heisel, William; Gakidou, Emmanuela; Vos, Theo; Forouzanfar, Mohammad; Schmidt, Jürgen; et al.
Table of contents I1 Introduction and aims of the workshop Christa Scheidt-Nave, Thomas Ziese, Judith Fuchs, Dietrich Plass S1 History, concept, and current results of GBD for Germany Tom Achoki, Katherine Leach-Kemon, Peter Speyer, William E. Heisel, Emmanuela Gakidou, Theo Vos S2 Methodology of the GBD 2013 Study–Mortality, Morbidity, Risk-Factors Mohammad Hossein Forouzanfar S3 National burden of disease surveillance examples of good practice: the case of Public Health England Jürgen C. Schmidt S4 Critical aspects of the burden of disease methodology and country-specific challenges Claudia E. Stein S5 Non-communicable disease surveillance in Germany – public health and data challenges Christa Scheidt-Nave, Elena von der Lippe, Benjamin Barnes, Markus Busch, Nina Buttmann-Schweiger, Judith Fuchs, Christin Heidemann, Klaus Kraywinkel, Enno Nowossadeck, Thomas Ziese S6 Different approaches in estimating the burden of communicable diseases using the examples of the healthcare associated infections and influenza Udo Buchholz, Matthias an der Heiden, Tim Eckmanns, Sebastian Haller S7 Behavioral and environmental attributable risk estimation Mohammad Hossein Forouzanfar S8 Environmental Burden of Disease (EBD) in Germany – past achievements and future perspectives Dietrich Plass, Myriam Tobollik, Dagmar Kallweit, Dirk Wintermeyer C1 Conclusions of the workshop Christa Scheidt-Nave, Thomas Ziese, Judith Fuchs, Dietrich Plass